Truancy, Psychosocial Distress, and Risk Behaviors in School‐Going Adolescents: Insights From a National School‐Based Survey in the Philippines - Dadras, Omid (Wiley, 2026)
Background
Truancy, or unexcused school absenteeism, is linked to adolescent psychosocial and behavioral problems and may serve as a behavioral marker of developmental and ecological vulnerability. This study examined associations between truancy and psychosocial distress, violence, limited social support, and substance use among Filipino students.
Methods
Data were drawn from the 2019 Philippines Global School-Based Student Health Survey (GSHS) of adolescents in Grades 7–10 (ages 13–17). Truancy was defined as missing school without permission during the past 30 days. Twenty-three variables covering psychosocial problems, violence, social support, and substance use were analyzed using logistic regression, stratified by sex.
Results
About 32.6% of students reported truancy in the past month, with higher odds among older and male adolescents. Truant students had elevated odds of loneliness, anxiety, suicidal behaviors, bullying, violence, and substance use. Female students exhibited higher odds of alcohol and marijuana use relative to males. Truant students were more likely to report limited parental support and peer isolation.
Implications for School Health Policy, Practice, and Equity
Recognizing truancy as an early warning marker can inform school-based screening, psychosocial support, and gender-sensitive interventions to reduce inequities.
Conclusions
Truancy may reflect underlying psychosocial challenges, underscoring the need for proactive, tiered school-based identification and support strategies for at-risk adolescents.